2000
DOI: 10.1164/ajrccm.162.3.9907120
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Measurements of Airway Dimensions and Emphysema in Smokers

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by the presence of airflow obstruction caused by emphysema or airway narrowing, or both. Low attenuation areas (LAA) on computed tomography (CT) have been shown to represent macroscopic or microscopic emphysema, or both. However CT has not been used to quantify the airway abnormalities in smokers with or without airflow obstruction. In this study, we used CT to evaluate both emphysema and airway wall thickening in 114 smokers. The CT measurements re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
587
9
10

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 633 publications
(629 citation statements)
references
References 29 publications
23
587
9
10
Order By: Relevance
“…We observed significant correlations between airway morphology and VDP in the RUL and RLL. Previous studies (25,26) have shown that RUL and RLL airway morphology is significantly correlated with whole-lung function (assessed by spirometry) in COPD, but these studies did not investigate regional relationships with function. The observation that thickened airway walls and narrowed airway lumens correlate with increasing ventilation heterogeneity in the RUL, and RLL suggests that there may be a structure-function relationship between airway morphology and ventilation in exsmokers.…”
Section: Discussionmentioning
confidence: 98%
“…We observed significant correlations between airway morphology and VDP in the RUL and RLL. Previous studies (25,26) have shown that RUL and RLL airway morphology is significantly correlated with whole-lung function (assessed by spirometry) in COPD, but these studies did not investigate regional relationships with function. The observation that thickened airway walls and narrowed airway lumens correlate with increasing ventilation heterogeneity in the RUL, and RLL suggests that there may be a structure-function relationship between airway morphology and ventilation in exsmokers.…”
Section: Discussionmentioning
confidence: 98%
“…NIIMI et al [72] showed progressive thickening of the wall of the right apical segmental bronchus in asthmatics as a function of disease severity (baseline FEV1), but, surprisingly, there was no difference in the luminal area of this airway in the severe asthmatics compared with the control subjects or mild asthmatics. Interestingly, for a given degree of airflow obstruction, the airway wall of the right apical bronchus is substantially thicker in asthmatics compared with COPD patients [18,72].…”
Section: Airway Imaging In Asthma Airway Dimensionsmentioning
confidence: 99%
“…2) [18,19]. Although this method provides a standardised and unbiased measurement, it has limitations.…”
Section: Quantitative Assessment Of Larger Airwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Severity of emphysema was determined from high-resolution computed tomography (HRCT) scans obtained at full inspiration. The percentage of the low attenuation area (%LAA) was calculated to assess the extent of emphysema, using HRCT scans according to Nakano et al, 12 with a minor modification. Briefly, six slices were obtained from the bilateral lungs at the upper, middle and lower lobes.…”
Section: Pulmonary Function Parametersmentioning
confidence: 99%